Exploring the decolonial imaginary: four transnational lives - Bray, Karen (The journal for cultural and religious theory, 2014)
A book profile of Patricia A. Schechter, Exploring the Decolonial Imaginary: Four Transnational Lives. New York: Palgrave Macmillan, 2011. 284 pp. ISBN: 978-0-230-33877-7